Pengembangan Media Pembelajaran Melalui Google Sites untuk Meningkatkan Kemampuan Menulis Teks Persuasif di UPTD SMP Negeri 6 Gunungsitoli - Gea, Nurman Samehuni; Ndruru, Mastawati; Bawamenewi, Arozatulo; Riana, Riana (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to develop learning media through Google Sites to Improve Persuasive Text Writing Skills at UPTD SMP Negeri 6 Gunungsitoli. The method used in this research is research and development (Research & Development). The developed learning media follow the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research results show that the developed learning media has undergone a validation process by three experts: a content expert, a language expert, and a design expert. The validation results indicate that the content expert gave a score of 94.7%, the language expert gave a score of 92%, and the design expert gave a score of 95%. These percentages show that the developed Google Sites learning media meets the feasibility criteria in terms of content, language, and design appearance. The practicality of the learning media was tested through two stages, namely small group testing (100%), and field trials (100%). The practicality of the learning media was tested through two stages, namely small group testing (100%), and field trials (100%). The effectiveness of the learning media was measured by the learning completeness of the students after using the Google Sites learning media. The results showed a completeness rate of 100% in small group trials, and 100% in field trials. This proves that the Google Sites learning media is effective, practical, and efficient for use in the learning process.